KONSEP PEMBINAAN BIARAWATI : STUDI KASUS RSCJ (Religious Of The Sacred Heart Of Jesus) BANDUNG: Studi Kasus Religious of the Sacred Heart of Jesus Bandung - Kholid Karomi; Abdullah Muslich Rizal Maulana; Putri Nurul Faizah; Tasya Azheda Arni Prameswari; Aanisah Cahyaning Almaas; Mahayu Fanieda; Amelda Dahni (Melo: Jurnal Studi Agama-agama, 2022)
Abstract : This study aimed to understand the stages of women becoming a nun in RSCJ Bandung. This study’s data collection technique was qualitative with a phenomenological approach. The author also interviewed two RSCJ nuns who have attained permanent and first vocations. As Servant of Christ who was willing to dedicate their lives to God, nuns had a convent life that was different from other people, following the vows that had been professed, such as devotion directed to God of various kinds, helping others, hand in hand with one another and being active in society based on the knowledge and spiritual level. Before dedicating themselves to society, nuns needed guidance to obtain provisions carried out during their service period. This study concluded that at RSCJ Bandung, prospective nuns received a lot of guidance and accordance with their respective fields, which are mastered with an emphasis on education vows because it is hoped that nuns will be able to teach others what they have learned while at RSCJ. Keys Words: nuns, formation, and vocations